Healthcare and productivity costs among Canadian road trauma survivors over the year following injury - Somayeh Momenyan; Herbert Chan; John A. Taylor; John A. Staples; Stirling Bryan; Devin R. Harris; Jeffrey R. Brubacher (Scientific Reports)
Abstract Understanding the economic burden of road trauma (RT) can support healthcare and traffic policy. This prospective cohort study enrolled 1480 RT survivors in British Columbia, Canada. Healthcare and lost productivity costs were estimated in 2023 Canadian dollars. Productivity loss was measured at 2, 4, 6, and 12 months post-injury. Potential predictors included sociodemographic, psychological, medical, and trauma factors. Outcomes were analyzed with a generalized linear model and quantile regression. We found that average healthcare costs during the year following RT were $19,280 (median $3,791). Average lost productivity cost for people employed when injured was $4,390 (median $1,011). Older age, lower health-related quality of life (HRQoL), ≥ 2 comorbidities, Injury Severity Score (ISS) ≥ 9, Glasgow Coma Scale ≤ 13, and torso injury were significantly associated with higher healthcare costs. Employed participants had lower healthcare costs. Older age, being female, lower HRQoL, ≥ 2 comorbidities, ISS ≥ 9, spine/back and upper extremity injuries were significantly associated with higher lost productivity costs. These factors were more strongly associated with greater costs at the upper quantiles. This study highlights the economic burden of RT injuries and identifies factors associated with higher costs.